The postscript murders [compact disc, unabridged] - Griffiths, Elly (Houghton Mifflin Harcourt Audio, 2021)
The death of a ninety-year-old woman with a heart condition should absolutely not be suspicious. DS Harbinder Kaur certainly sees nothing to concern her in carer Natalka's account of Peggy Smith's death. But Natalka reveals that Peggy lied about her heart condition and that she had been sure someone was following her, and that Peggy Smith had been a 'murder consultant' who plotted deaths for authors, and knew more about murder than anyone has any right to... When clearing out Peggy's flat ends in Natalka being held at gunpoint by a masked figure, DS Harbinder Kaur thinks that maybe there is no such thing as an unsuspicious death after all.